What is the Universe Like? - Narlikar, J.V. (SCHOOL SCIENCE, 2013)
I have chosen the title “What is the universe like?” I should have added a few more words to it and said “What is the universe like to an astronomer or to an astrophysicist?” because the universe by itself means everything and it would mean a different thing to different people. So it will not be possible for anyone to do justice with the title as it stands and, therefore, I would like to say right in the beginning that I want to give you an astronomer’s view of the universe: which is the large scale structure of the universe. Now, if you look at the night sky you see stars, the planets and the moon; but you should also be aware of the fact that there is a lot in the space which your eyes cannot see. It is because the human eyes have limitations imposed by their biological construction. Man is aware of these limitations and has invented the telescope and various other types of apparatus which help him to observe the universe.